Diagnostic and prognostic biomarkers and therapeutic targets in melanoma - Murphy, Michael J. (Current Clinical Pathology, 2012)
This book describes both the technologies used in the discovery of melanoma biomarkers and the clinical application of these biomarkers for diagnosis and staging of disease, determination of prognosis, treatment planning, monitoring of response to therapy, identification of novel therapeutic targets and drug development. A broad range of biomarkers (DNA/chromosomal, mRNA, microRNA, mitochondrial DNA, epigenetic and protein) is outlined. As therapies for melanoma become increasingly more target specific, the identification, validation and use of biomarkers will invariably play a greater role in the management of patients with this disease. Diagnostic and Prognostic Biomarkers and Therapeutic Targets in Melanoma is an essential resource for oncologists, dermatologists, dermatopathologists, general pathologists with an interest in melanoma, and melanoma researchers.